Quadratic Formula

Thread Starter

Thinker

Joined Jan 9, 2007
62
Okay.

I have to solve a algebraic expression using a quadratic formula.

This is it:

X2 - 2X - 6 = 0

I used the quadratic formula on your site here to help me. So...

a=1, b=-2, c=-6


X= +3 ± |4 - 4 * 1 - (-6)
-------------------------
2 * 1

= 3 ± |0
----------
2

= 3 ± 0
--------
2

.........and I got 1.5

But when i put it to the equation X2 - 2X - 6 = 0 I get 0.75, it should be 0 right?

Does anybody know where i possible went wrong?
 

Dave

Joined Nov 17, 2003
6,970
Hi Thinker,

You appear to be a little off course with this one. Papabravo is correct: --2 = +2. Additionally, what you have in the square root is wrong:

If b = -2, then b^2 = +4

And if a = 1 and c = -6, then 4ac = 4*1*-6 = -24

So your expression in the square root is (4 - -24) = +28

If you follow the quadratic equation exactly you should get the answer to be x = +3.64575 or -1.64575

Have another go and post up if you have any problems.

Dave
 

Thread Starter

Thinker

Joined Jan 9, 2007
62
Okay i worked everything out again and this is what i got:

(3.64575)2 - (2 * 3.64575) - 6 = 0
13.29150 - 7.2915 - 6 = 0

That is for the 3.64575 answer. I don't know what i was thinking when i put -3 in the equation instead of -2! :confused:

Thanks Dave and for the help. :)
 

Dave

Joined Nov 17, 2003
6,970
That is for the 3.64575 answer. I don't know what i was thinking when i put -3 in the equation instead of -2! :confused:
Don't forget that x = -1.64575 is also a solution to the equation. This arises due to the fact that there is a +/- in the quadratic formula and provided 4ac =/ 0 then there will be two solutions.

Dave
 
Top